Trial by media: participatory justice in a networked world - Gies, Lieve (Palgrave studies in crime, media and culture, 2025)
Chapter 1. Introduction: Understanding trial by media and participatory justice in a networked world (Lieve Gies) -- Part I: Legacy media and the court of public opinion -- Chapter 2. Websleuthing before the web? Pre-digital sleuthing in public writing about Australia’s dingo baby case (Belinda Middleweek) -- Chapter 3. Trial by film: Cases and causes in popular legal culture (Stefan Machura) -- Chapter 4. Between a rock and a hard place: Israel’s courtroom journalists in the digital age (Anat Peleg) -- Part II: Social media and the perils of amateur sleuthing -- Chapter 5. The complexities of trial by social media: Examining the connection between self-exposure and harassment (Azi Lev-on) -- Chapter 6 A gendered media spectacle for the digital era: Nicola Bulley, ‘missing white woman syndrome’ and middle-class, middle-aged, menopausal womanhood on trial (Tanya Horeck and Deborah Jermyn) -- Chapter 7 Playing their own private detectives: Digital witnessing, forensic fandom and true crime narratives (Bethan Jones and Steff El Madawi) -- Part III: Media campaigns for justice -- Chapter 8. “How we brought down a war criminal”: Defamation trials as an alternative space for justice (Maria Rae) -- Chapter 9. The paradox of true crime podcasting: Advocacy, prejudice, and the pursuit of justice (Katrina Clifford) -- Chapter 10. When is trial by media not trial by media?: Seeking justice for Sanda Dia in post-Dutroux Belgium (Lieve Gies) -- Part IV: Impacts of trial by media -- Chapter 11. The impact of media publicity on the presumption of innocence (Maria Stoyanova) -- Chapter 12. The critical-forensic linguistic interface and the Spectrum of Trial by Media: Media-made sexual assault in the courtroom (Simon Statham) -- Chapter 13. Publicity and legitimacy of public international law: The role of media in international legal proceedings (Paolo Vargiu).